Transportation and Its Ethical Problem - Wibowo, Wahyu; A. Silalahi, Siska; Lestari Ningrum, Selli (STMT Trisakti, 2014)
Transportation problem is a common problem in modern life. The impact of increasingly severe traffic congestion, for example, shows the transport problems are inevitable. However, when the problem is transformed into an ethical problem, it can be said that the ethos of the nation is in danger of experiencing a slump. Phenomenological method of research through language is used with the basis of the speech act theory of communication, after tracing automotive advertising published by newspaper in Jakarta (from March 2013 to March 2014), the result shows that Indonesian transportation latest ethical problem leads to a conspiracy carried out by the newspapers and the advertisers. Keywords: transportation, phenomenological language, speech act theory of communication, advertising.